Consumers attitudes to Iberian pork meat - Martínez B.; Rubio B.; Vaquero M.; Sánchez M.J. (7th International Symposium on the Mediterranean Pig, 2012)
In the last years, Iberian pork consumption has been limited as a result of relations established between fat consumption and cardiovascular diseases. However, recent researches have allowed establishing healthy properties to the intake of these kind of meat, and as a consequence its sale has increased, competing successfully with other meats. The objective of this study was to determine the attitudes of consumers to Iberian pork meat. To assess consumers’ behaviour to breed (Iberian and white pig) and anatomical origin of the pieces commercial ("pluma", "presa", "secreto") of Iberian pork meat, discriminate tests were used in order to detect differences. Besides, an affective test was carried out in order to know the consumers preference to feeding of the Iberian pigs ("bellota", "cebo"). The results obtained in the triangle tests showed that consumers were able to differentiate between Iberian and white pork loin. Also differences were found between different commercial cuts of Iberian pig. However, consumers didn’t show preferences regarding feeding of the Iberian pigs.
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)